2010
DOI: 10.1098/rstb.2009.0211
|View full text |Cite
|
Sign up to set email alerts
|

Using ecology to guide the study of cognitive and neural mechanisms of different aspects of spatial memory in food-hoarding animals

Abstract: Understanding the survival value of behaviour does not tell us how the mechanisms that control this behaviour work. Nevertheless, understanding survival value can guide the study of these mechanisms. In this paper, we apply this principle to understanding the cognitive mechanisms that support cache retrieval in scatter-hoarding animals. We believe it is too simplistic to predict that all scatter-hoarding animals will outperform non-hoarding animals on all tests of spatial memory. Instead, we argue that we shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 143 publications
(182 reference statements)
2
62
0
Order By: Relevance
“…One possible behavioural mechanism that could allow animals to reduce the rate of memory deterioration over time, and therefore remember cache locations over many months, is to repeatedly revisit cache sites to reinforce spatial memory (Huston & Oitzl 1989;Smulders et al 2010;Roth et al 2012), henceforth the 'memory enhancement hypothesis'. Roth et al (2012) speculated that the failure of prior studies to detect longterm memory abilities in parids was due to the one-trial nature of the studies.…”
mentioning
confidence: 99%
“…One possible behavioural mechanism that could allow animals to reduce the rate of memory deterioration over time, and therefore remember cache locations over many months, is to repeatedly revisit cache sites to reinforce spatial memory (Huston & Oitzl 1989;Smulders et al 2010;Roth et al 2012), henceforth the 'memory enhancement hypothesis'. Roth et al (2012) speculated that the failure of prior studies to detect longterm memory abilities in parids was due to the one-trial nature of the studies.…”
mentioning
confidence: 99%
“…Results of behavioural tests appeared inconclusive, as some studies have reported that caching species indeed perform better on spatial memory tasks while a few studies failed to support superiority of food-caching species (reviewed by Shettleworth 1995; . A potential cause of these apparent discrepancies is discussed by Smulders et al (2010).…”
Section: Adaptive Specialization Of Memory and The Hippocampusmentioning
confidence: 99%
“…The article by Smulders et al (2010) as well as that by Roth et al (2010a) provide a discussion of the problems associated with the current approach to linking the hippocampus to the adaptive specialization hypothesis. Smulders et al (2010) argue that the comparisons to date have used an oversimplified approach by looking for a single cognitive adaptation that applies to all aspects of spatial memory and across all foodhoarding species.…”
Section: Adaptive Specialization Of Memory and The Hippocampusmentioning
confidence: 99%
See 2 more Smart Citations